Determinan Kualitas Air terhadap Penggunaan Air Bersih dalam Rumah Tangga - Yusuf Hanafi Lubis; Nafisah Khan; Mayadrie Aidhi Aridzki; Alifia Nadhira; Abdulkarim Batubara (Universitas Batanghari Jambi, 2023)
People in Indonesia itself from several regions are still unable to enjoy the availability of clean water in meeting their daily household needs. This study aims to examine water quality problems in the use of clean water in households in Tangkahan Village, Medan Labuhan District. The method used a direct survey with cross-sectional research design with the criteria of people domiciled in Tangkahan Village. Samples were collected through direct interviews using questionnaires and then the data were analyzed descriptively of frequency and bivariate. The results showed that almost half of the respondents who felt comfortable after drinking dirty water and were at risk 2.47 times. This study concludes that more than 50% of people have low water quality in their households and that communities and local government leaders must be diligent in carrying out mutual cooperation to clean up water facilities in the local environment.